Single‐cell and spatial alterations of neural cells and circuits in clinical and translational medicine - William Wang; Xuanqi Liu; Diane Catherine Wang (Clinical and Translational Medicine, 2024)
Abstract The spatiotemporal heterogeneity of neurons, circuits and regulators is being uncovered at a single‐cell level, from single‐cell gene expression to functional regulations. The classifications, architectonics and functional communications amongst neural cells and circuits within the brain can be clearly delineated using single‐cell multiomics and transomics. This Editorial highlights the spatiotemporal heterogeneity of neurons and circuits as well as regulators, initiates the translation of neuronal diversity and spatial organisation at single‐cell levels into clinical considerations, and enables the discovery and development of new therapies for neurological diseases. It is predicted that single‐cell and spatial multiomics will be integrated with metabolomic profiles and corresponding gene epigenetic modifications. The interactions amongst DNAs, RNAs and proteins in a cell provide details of intracellular functional regulations and new opportunities for the translation of temporospatial diversity of neural cell subtypes/states into clinical practice. The application of single‐cell multiomics with four‐dimensional genome to the human pathological brain will lead us to a new milestone of the diagnosis and treatment.